The Trading Axis in Irkutsk Downtown - Grigoryeva, Elena (project baikal, 2015)
The article reveals a linear concentration of the trading function in the historical center of Irkutsk. It features historical prerequisites and continuation of the tradition in the post-Soviet period, given the conversion of plants and factories. The article analyses the current state and prospects of modernization of the trading axis with its transformation into a modern public space.